A Competitive System: Graduate Student Recruitment in STEM and Why Money May Not be the Answer. (18th September 2020) - Wall Bortz, Whitney E.; Knight, David B.; Lyles, Chelsea H.; Kinoshita, Timothy; Choe, Nathan H.; Denton, Maya; Borrego, Maura
ABSTRACT: Doctoral student recruitment is a dynamic, complex, and under-researched phenomenon. There is steep competition between programs for recruiting students with large amounts of resources at stake, especially within the STEM fields, and programs do not operate in isolation within such environments. In this paper, we explore how graduate programs position themselves relative to other programs as they recruit STEM doctoral students. Drawing from 47 interviews with graduate program leaders, 49 interviews with graduate students, and 63 questionnaire responses from graduate program staff and administrators, this research analyzes common recruitment practices of STEM doctoral programs alongside student perspectives about their decision processes. We reveal how competitive forces may lead programs to adopt non-evidence-based recruitment strategies that may not align with either program leaders' stated values or students' priorities. Although program leaders expressed the importance of students prioritizing academic factors in their decisions, our data revealed that programs commonly utilize financial resources as their main recruitment mechanism in practice. By demonstrating this incongruence, our paper aims to illuminate a potential blind spot so programs might choose to change seemingly institutionalized processes that may be out of alignment with their own stated values and those of the students they are seeking to recruit.